(untitled) (International journal of artificial intelligence, 2026)
The article is devoted to the issues of staging works on historical themes in Uzbek dramaturgy and theaters, and it is examined through the example of Nasrullo Qobilov dramatic work “Na malakman na farishta” The article discusses the difficulty of creating works on historical themes, as well as how historical sources, enriched with artistic interpretation, help the audience gain a deeper understanding of the main idea of the work. Any work possessing artistic value has an enduring legacy. The article also emphasizes that newly created dramatic works should be of high artistic quality and addresses the issues of their broader implementation.